ANALISIS KEKUATAN PENGARUH MODEL BRACING TERHADAP PONDASI KATROL LADDER PADA KAPAL ISAP PRODUKSI (KIP) - Hariyono Yono; Azhar Aras Mubarak (Construction and Material Journal, 2022)
With the use of the bracing model that was built during the building of the ladder-pulley foundation, this research intends to analyze the strength of the ladder-pulley foundation on the Kapal Isap Produksi (KIP). Finite element analysis (FEA) and modeling with the Ansys software were used in the investigation. The 58 m length of the actual ladder is considered when creating the model. Then, create each model of a diagonal brace and an x-bracing specifically for the pulley foundation. After that, a special diagonal brace and an x-bracing model were developed, respectively, for the pulley foundation's building. The load acting on the ladder for the two versions is the same: 1.42 x 105 N for the pipe and mud, 0.57 x 105 N for the cutter, and 0.67 x 108 Nmm for the cutter torque. According to the analysis's findings, the diagonal brace model's strut component experiences the highest level of stress, measuring 57.32 N/mm2, whereas the x-bracing model's greatest stress value is 25.44 N/mm2. These findings suggest that, to reduce structural failure in the ladder pulley area, it is preferable to use x-bracing construction for the brace design put there. This is because it has a lower minimum stress value than the diagonal brace model. Keywords: Bracing, Ladder, KIP, FEA.